2018
DOI: 10.1021/acs.jmedchem.8b00909
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of MD-224 as a First-in-Class, Highly Potent, and Efficacious Proteolysis Targeting Chimera Murine Double Minute 2 Degrader Capable of Achieving Complete and Durable Tumor Regression

Abstract: Human murine double minute 2 (MDM2) protein is a primary endogenous cellular inhibitor of the tumor suppressor p53 and has been pursued as an attractive cancer therapeutic target. Several potent, non-peptide small-molecule inhibitors of MDM2 are currently in clinical development. In this paper, we report our design, synthesis and evaluation of small-molecule MDM2 degraders based on the proteolysis targeting chimera (PROTAC) concept. The most promising compound (MD-224) effectively induces rapid degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
183
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(200 citation statements)
references
References 46 publications
5
183
0
Order By: Relevance
“…In a recent study on MDM2-targeting PROTACs based on the MDM2-p53 interaction inhibitor MI-1061 and cereblon ligands, a similar effect was observed for some of the PROTACS. 21 Consistent with the results of the Western blots, HCT-116 cells treated with 2 showed a higher degree of apoptosis than cells treated with 1 did (39 AE 7% apoptotic cells for 30 mM 2 vs. 15 AE 1% for 30 mM 1, Fig. 5A and Fig.…”
supporting
confidence: 88%
“…In a recent study on MDM2-targeting PROTACs based on the MDM2-p53 interaction inhibitor MI-1061 and cereblon ligands, a similar effect was observed for some of the PROTACS. 21 Consistent with the results of the Western blots, HCT-116 cells treated with 2 showed a higher degree of apoptosis than cells treated with 1 did (39 AE 7% apoptotic cells for 30 mM 2 vs. 15 AE 1% for 30 mM 1, Fig. 5A and Fig.…”
supporting
confidence: 88%
“…Currently, several other drug discovery strategies have also been attempted, including modulating MDM2's E3 ubiquitin ligase activity, inducing MDM2 autoubiquitination, inhibiting the MDM2/MDMX interaction, blocking MDM2 gene expression, and MDM2 degraders based on the proteolysis targeting chimera concept . However, MDM2 has been shown to exert pathogenic effects through both p53‐dependent and p53‐independent mechanisms.…”
Section: General Discussion and Future Research Directionsmentioning
confidence: 99%
“…It is noteworthy that a recent study reported MDM2 PROTAC degraders, designed by linking an MDM2 inhibitor via either a thalidomide-based CRBN ligand or a VHL ligand. 57 Potent and selective PROTAC-induced degradation of MDM2 was observed for the CRBN-MDM2 heterodimers. However notably, protein level of the hijacked CRBN or VHL ligases were not monitored.…”
Section: Discussionmentioning
confidence: 93%
“…However notably, protein level of the hijacked CRBN or VHL ligases were not monitored. 57 Future work is warranted to interrogate many more combinations of E3 ligases and hetero-dimerizer compounds to bring them together. Given the number of E3 ligases predicted to function in cells (up to 600) this approach could speed up our ability to chemically intervene on E3 ligase themselves using targeted protein degradation, with both biological and therapeutic benefits.…”
Section: Discussionmentioning
confidence: 99%